Comparing the Fiscal Consequences of Controlled and Uncontrolled Osteoarthritis Pain Applying a UK Public Economic Perspective - Rui Martins; Nikos Kotsopoulos; Melodi Kosaner Kließ; Craig Beck; Lucy Abraham; Samuel Large; Patricia Schepman; Mark P. Connolly (Journal of Health Economics and Outcomes Research)
**Background:** Individuals experiencing osteoarthritis (OA) pain can pose significant costs for governments due to reduced work activity in these individuals and increasing reliance on public support benefits. In this analysis we capture the broader economic impact of OA pain by applying a government perspective, public economic framework to assess controlled and uncontrolled pain.